2016
DOI: 10.1016/j.fuel.2015.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H 2 O, CO 2 and O 2 addition on biomass gasification in entrained flow reactor conditions: Experiments and modelling

Abstract: . Influence of H2O, CO2 and O-2 addition on biomass gasification in entrained flow reactor conditions: Experiments and modelling. Fuel, Elsevier, 2016, 166, pp.166-178. 10 Experiments were modelled with a 1D-model using detailed chemical scheme. Gas, char, tar + soot were satisfactorily simulated in the whole range of conditions. ysis reaction, gas phase reaction with a detailed chemical scheme (176 species, 5988 reactions), char gasification by steam and CO 2 and soot formation. H 2 O or CO addition has no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 27 publications
5
35
2
Order By: Relevance
“…This behavior can be explained by the sublimation/boiling of potassium during pyrolysis performed at 1400 • C (boiling point 1420 • C, sublimation at 1500 • C), leading to the appearance of large porosity at the surface of the char particle, or again to the char gasification by H 2 O/CO 2 formed during the pyrolysis stage. This is consistent with other results obtained under similar conditions [23], which also showed that potassium released from char at 1400 • C was incorporated into soot particles. The samples Char-500 and Char-600 present a smooth surface, comparable to the one of the raw biomass.…”
Section: Microscopic Analysis Of the Biochar Surfacessupporting
confidence: 93%
See 3 more Smart Citations
“…This behavior can be explained by the sublimation/boiling of potassium during pyrolysis performed at 1400 • C (boiling point 1420 • C, sublimation at 1500 • C), leading to the appearance of large porosity at the surface of the char particle, or again to the char gasification by H 2 O/CO 2 formed during the pyrolysis stage. This is consistent with other results obtained under similar conditions [23], which also showed that potassium released from char at 1400 • C was incorporated into soot particles. The samples Char-500 and Char-600 present a smooth surface, comparable to the one of the raw biomass.…”
Section: Microscopic Analysis Of the Biochar Surfacessupporting
confidence: 93%
“…Furthermore, at high temperatures, the formation of soot was observed, starting from 1000 °C. A deep analysis of the operating conditions' effect on the pyrolysis product distribution can be found in previous investigations [23,26]. The main focus of the present study was to identify the effect of the operating conditions on the char characteristics.…”
Section: Pyrolysis Product Yieldsmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, [7] investigated the gasification of pine sawdust using CO2 over Ni/Al precipitation catalyst. [8] studied the gasification of beech sawdust in the entrained flow reactor. [9] developed a model to investigate the performance of biomass gasification with CO2 using fluidized bed gasifier.…”
Section: Introductionmentioning
confidence: 99%